Antakakkavi Vīrarākamutaliār iyaṟṟiya Tiruvārūlā - Vīrarākava Mutaliyār, 17th cent (SAMP early 20th-century Indian books project, 1905)
Hymns in praise of Tyāgarāja, presiding deity at Tiruvālūr, India.